Small-scale mining production system design and socio-economic sustainability an application to Philippine gold and copper deposits - Compañero, Reinol Josef DC (2012)
The nature of the small-scale mining (SSM) or artisanal mining (ASM) industry in the Philippines have seen little development through the years. It is still characterized by rudimentary techniques in the processing of ore deposits leading to various environmental problems, social unacceptability, and still a vast untapped economic potential. One notable observation from a target site, given the nature of Philippine ore, is that only gold is recovered in this level of production and copper is essentially thrown away in the tailings. This study proposed improvements in the technical aspect of minerals processing and metal extraction, focused on local gold and copper-bearing ores, modified the existing production model and introduced an applicable technology which can promote sustainable improvement in the economic, environmental and social aspects of small-scale mining. The central concern dealt with in the current production scheme was the use of mercury (Hg) and Cyanide (CN-); issues arising from utilizing these reagents are already well-documented. A production system design based on flotation technology has been chosen as the better alternative for gold recovery due to its recent development for the said application as well as the advantage of proven functionality for copper recovery -- resulting in an addition of another stream of saleable product.